Postmortem Bleed - An Artefact- A Case Report (Journal of Forensic Medicine & Toxicology, 2026)
Introduction: Artefact is any change caused or feature introduced in a body after death (accidental or physiologically  unrelated finding to the natural state of the body) that is likely to lead to misinterpretation of medico legally significant  ante mortem findings.  Case details: This is a case of 24yr old male who hanged himself in a hotel room. Front foot were touching the floor  and heel slightly lifted up and there was frank blood on the floor just beneath the foot. Upon examining the body, dried  blood stains were present on both the lower limb and the origin of bleed was traced to anal orifice. After taking detailed  history the relatives mentioned that the person was suffering from hemorrhoids and was taking treatment for the same  from local hospital. During dissection anal mucosal tear was seen at 12’ O clock position. Multiple petechiae were also  seen on larynx and epiglo ttis. There were no signs of struggle or injury on body and the careful neck dissection did not  show any muscular haematoma or rupture of muscles. Conclusion: The time since death was about 24 to 36hr from time of postmortem examination. It was concluded as a post  mortem artefact, not an injury due to any foul play.
Keywords: Hanging; Hemorrhoids; Postmortem Bleed; Artefact